Contemporaneity Decolonizing Knowledge & Independency - Koh, Jay (Journal of Urban Culture Research, 2023)
This article discusses the platform and selected texts from Journal of Urban Culture Research (JUCR), in relation to contemporary turns from the 60s on participation and diversity in responses to the making of an open society to the 80s on decolonization of knowledge from the enlightenment trajectory. Only lately, these ideas of ’decolonization’ has gained traction in our regions and we need to be careful not to mix the meaning of this term with the fight for independence after the WWII by colonized nations or criticism of the concept of orientalism and the construction of racial stereotypes. Discussed turns on participation, diversity and decolonization are juxtaposed to issues and working in urban culture, the everyday, the cognitive and communicative qualities in the performance of the self, and the many others. This text includes discussion and exploration of critical structures in research and analytic processes, on reading theory-based and practice-based writings and relates these to art-making in traditional spaces and in real world situations.